Effects of polyvinylpyrrolidone as a dispersant agent of reduced graphene oxide on the properties of carbon fiber-reinforced polymer composites - Kaftelen-Odabasi, Hulya; Odabasi, Akin; Caballero-Briones, Felipe; Arvizu-Rodriguez, Liliana E.; Ozdemir, Mustafa; Baydogan, Murat (Sage Publications Ltd, 2023)
The electrical and mechanical properties of carbon fiber-reinforced polymer (CFRP) composites have a close dependence on the use of modifiers like polyvinylpyrrolidone (PVP), as well as on the processing techniques to disperse functional charges such as graphene-related materials into the epoxy base. In the present work, reduced graphene oxide (RGO), prepared by a natural antioxidant agent, astaxanthin, was used as a filler material in the epoxy matrix of the carbon fiber composites. The astaxanthin reduction leads to an increase in the sp2ordering in RGO; some residual epoxy and C-O groups that enhance the interaction with the epoxy matrix remain after reduction. The effects of RGO and PVP-modified RGO (PVP-RGO)fillers with different contents(0.05, 0.1, and 0.15% wt.) on the electrical conductivity, bending properties, and dynamic mechanical properties of CFRP were investigated. The incorporation of 0.15 wt.% RGO with and without PVP-modification, leads to through-the-thickness (Z-direction testing) conductivity values 7.4 and 9.6 times higher than those of the neat composite, respectively. The conductivity tests indicate that the RGO/epoxy composite behaves as a continuous conductor due to the formation of agglomerates of RGO within the matrix, while at the added contents of the PVP-RGO filler, the composite is below the percolation threshold, then conducting by electron tunneling, due to a better dispersion of the PVP-RGO filler within the epoxy matrix. The dynamic mechanical analysis shows that the glass transition temperature is indicative of the interactions among the filler, the epoxy matrix, and the carbon fiber, that is, the PVP-RGO filler increases the chain mobility due to its higher dispersion in the matrix. While T(g )of the neat epoxy/CFRP composite is 92.5 degrees C, a minimum T-g of 88.5 degrees C was achieved with a 0.10 % wt. PVP-RGO filler contents, and a maximum Tgof94.5 degrees C with a 0.15 % wt. of RGO filler amount. For constantfiller content (0.15 wt.%), CFRP composite containing RGO and PVP-modified RGO exhibited 9.73% and 13.87% increase inflexural strength values, respectively, compared to the neat composite. Thebending test revealed that PVP modification to RGO is beneficial to improveflexural strength of CFRP composites.
Keywords: Reduced graphene oxide; polyvinylpyrrolidone; carbon fiber composites; mechanical properties; glass transition; electrical properties